Solubility and Dissolution Enhancement of Atorvastatin Calcium using Phospholipid Solid Dispersion Technique - Bashar K. K. Ghyadh; Al-Khedairy, Eman (Iraqi Journal of Pharmaceutical Sciences, 2023)
Atorvastatin (ATR) is a poorly water-soluble anti-hyperlipidemic drug. The drug belongs to the class II group according to the biopharmaceutical classification system (BCS) with low bioavailability due to its low solubility. Solid dispersion is an effective technique for enhancing the solubility and dissolution of drugs. Phospholipid solid dispersion (PSD) using phosphatidylcholine (PC) as a carrier with or without adsorbent (magnesium aluminum silicate, silicon dioxide 15nm, silicon dioxide 30nm, calcium silicate) was used to prepare ATR PSD using different drug: PC: adsorbent ratios by solvent evaporation method. The resulted PSD was evaluated for its percentage yield, drug content, solubility, dissolution rate, Fourier transformation infrared spectroscopy (FTIR), powder X-ray diffraction study (PXRD), and differential scanning calorimetry (DSC). The prepared (PSD) showed improvement in drug solubility in all prepared formulas. The best result was obtained with F5 (ATR: PC: MAS 1:3:4). The solubility was increased by 21 folds compared to the pure drug with enhanced dissolution and decrease crystallinity.